(untitled) (Bangladesh Pharmaceutical Journal, 2023)
The main target of this current research work was intended to construct and make affirmation of a facile, economical, very sensitive with high precision and accuracy, reversed-phase high performance liquid chromatographic method for simultaneous estimation of two drugs Ramipril and Carvedilol. The validation parameters were verified based on the standard requirements of International Council for Harmonization (ICH), U.S. Food and Drug Administration (FDA) and United States Pharmacopoeia (USP) by the determination of linearity, accuracy and precision. To develop the method, a C18 column (with a dimension of 250 × 4.6 mm, 5 μ, SUFELCOSILTM LC-18) was used. The mobile phase was comprised of aqueous KH2PO4 buffer solution and acetonitrile at the ratio of 55:45 (V/V) and flow rate was 1 mL per minute. 220 nm wavelength in the ultra-violet region was used to monitor the effluents and the retention times were found at 5.1±0.1 and 8.1±0.1 minutes for Ramipril and Carvedilol, respectively. Percent recovery for both drugs was above 98%, which demonstrated that the accuracy protocol was maintained. The linearity responses of the method for both Ramipril and Carvedilol were higher than 0.995 and the percentage of Relative Standard Deviation (RSD) (precision) for both of these two drugs were lower than the highest permissible limit or less than 2% (according to FDA). Therefore, it is easily perceptible that the corresponding RP-HPLC method was highly accurate, effective, rapid and precise which can offer huge potential for the application of simultaneous assay of Ramipril and Carvedilol in pure forms. Bangladesh Pharmaceutical Journal 26(1): 15-19, 2023 (January)